Tourism Development Strategy in Kemiren Village in Banyuwangi - Lubis, Lunariana (European Publisher, 2019)
Local wisdom-based tourism is one form of tourism that has been developed in Indonesia. One of the local wisdom-based tourism in Indonesia is located in Kemiren Village, Banyuwangi, East Java. In addition to nature tourism, Kemiren Village also has local wisdom in the form of cultural tourism potential such as Barong Ider Bumi dancing, Kopi Sepuluh Ewu Festival, Gandrung dancing, and Angklung Paglak. The number of tourists both local and foreign tourists visiting Kemiren Village has experienced ups and downs caused by various things and obstacles that may be faced in the development of existing tourist attractions, both in management and in their use. This makes the writer want to examine the efforts and strategies of Department of Cultures and Tourism in Banyuwangi to develop the potential tourism of Kemiren village. Qualitative research is used as the research method using case study. Based on the findings through observation, interview and documentation, it is found that the tourism development in Kemiren village in Banyuwangi is from the development of objects and tourism, the development and renewable on tourism infrastructure for creating Kemiren village as the tourism destination for national and international visitors.